Management of communal property of united territorial communities in the context of new challenges of local government reform - Shkilnyak, Mykhaylo; Vasina, Alla; Monastyrskyi, Grygorii; Avhustyn, Ruslan; Dudkina, Olena (Herald of Economics, 2020)
Analytical note based on the materials of the regional round table.The meeting of the regional round table took place on September 16, 2020 online using the ZOOM platform.